Electrical properties of cobalt contact to p-GaN - Kim, JW; Won, JH; Park, SY; Kim, SI; Choi, IH (KOREAN PHYSICAL SOC, 2001)
The effects of rapid thermal annealing (RTA) oil Co/p-GaN contacts in an O-2/N-2 atmosphere without intermediate metal were investigated. It was observed that the contact resistance decreased with increasing RTA temperature and that the resistance was reduced by a factor of about 30 after RTA at 600 degreesC in the O-2/N-2 atmosphere. The specific minimum contact resistance was about 10(-2) Omega .cm(2) range. Comparison of the R-0 and p(c) values revealed that the rapid thermal annealing ill the O-2/N-2 was more effective for reducing the contact resistance than the normal furnace annealing. The reason for the reduction of resistance was expected to bo the increase of hole concentration due to the highly reactivated removal of hydrogen atoms in the p-GaN by RTA in thc O-2/N-2 atmosphere.
Keywords: HETEROSTRUCTURES; ALXGA1-XN